Isothermal precipitation kinetics of carbides in undercooled austenite and ferrite of a titanium microalloyed steel. (15th October 2016) - Peng, Zhengwu; Li, Liejun; Chen, Songjun; Huo, Xiangdong; Gao, Jixiang
Abstract: A new method for isothermal precipitation kinetics of carbides in undercooled austenite and ferrite has been established based on measuring the strength increments. Precipitation-time-temperature (PTT) diagrams of carbides were determined with this method performed on a Gleeble simulator, for a low-carbon titanium microalloyed steel in a temperature range from 530 °C to 670 °C. Fine precipitates were studied by using high resolution transmission electron microscope (HRTEM), and their volume fractions together with their attributions to strength increments were calculated and analyzed. Results show that the strength increments are mainly attributed to the γ/α interphase precipitation whose nano-scale TiC precipitates obey the Baker-Nutting orientation relationship with respect to the ferrite matrix: (100)TiC ǁ (100)α-Fe and [011]TiC ǁ [001]α-Fe . The PTT curves obtained have a classic C-shape with their noses at about 600 °C, where the strength increment reaches 114 MPa after isothermally holding for 1 h. Additionally, the corresponding precipitation kinetics curves are presented in an S-shape, and a modified-form of Avrami formula is introduced to describe their growth periods. The presented mathematical expression fits the experimental data quite well. Consequently, the proposed new method is intuitive, effective and convenient, particularly suitable for detecting the precipitation kinetics in low temperature range. Graphical abstract: Highlights: A new method for isothermal precipitation kinetics of carbides in ferrite is first proposed. Precipitation-time-temperature diagrams of carbides in ferrite are determined efficiently. A modified-form of Avrami formula is developed to describe the precipitation kinetic curves. Isothermal precipitation occurs preferentially at sub-boundaries and dislocations, then γ/α interphase and point defects. Strength increment is mainly attributed to interphase precipitation for a low-carbon titanium microalloyed steel.